Determinación de los beneficios socioeconómico que genera la comercialización de los productores de licor artesanal en el recinto Guachana parroquia Guanujo en el periodo 2017 - Ramírez Patín, Jessenia Verónica (2018)
The research was based on the problem of how the commercialization of artisan liquor affects the socioeconomic benefits of the inhabitants of the Guachana Precinct, Guanujo Parish. The sector of Guachana is characterized by having enterprising people which motivated us to carry out the study focused on identifying the factors that influence the commercialization of artisanal liquor and therefore to know if it is profitable to carry out this activity, through this research the benefits are determined that exist in the marketing of said product. The methods that were considered for the realization of this project are: Historical Method, Deductive and Inductive. The types of research that were determined are: Field research, Quantitative, Qualitative, Descriptive and Bibliographic. The research techniques and instruments were the surveys applied to the Guachana producers. Through research, the different socioeconomic factors that most influenced the commercialization of artisanal liquor were determined, with the social factor being the most relevant and the motivation since this element is fundamental for undertaking any business. This activity is carried out by producers out of necessity and to obtain profitability to support their families and improve the quality of life. Among the sources of financing used by producers are loans to cooperatives, family savings and own capital usually prefer these means of financing because it gives them ease and agility to undertake. Currently the producers are going through an economic crisis due to the laws imposed by the government, this causes their income to be low and unprofitable for that reason they are dedicated to the manufacture of panelas, agriculture and livestock to cover the necessary expenses of their families, in the same way they do not have a fixed price on their products, which causes problems for their proper commercialization.